Phenotypic characterisation of canine epileptoid cramping syndrome in the Border terrier. (26th December 2013) - Black, V.; Garosi, L.; Lowrie, M.; Harvey, R. J.; Gale, J.
<x xml:space="preserve">Abstract</x> OBJECTIVES To characterise the phenotype of Border terriers suspected to be affected by canine epileptoid cramping syndrome and to identify possible contributing factors. METHODS Owners of Border terriers with suspected canine epileptoid cramping syndrome were invited to complete an online questionnaire. The results of these responses were collated and analysed. RESULTS Twenty‐nine Border terriers were included. Most affected dogs had their first episode before 3 years of age (range: 0·2 to 7·0 years). The majority of episodes lasted between 2 and 30 minutes (range: 0·5 to 150 minutes). The most frequent observations during the episodes were difficulty in walking (27 of 29), mild tremor (21 of 29) and dystonia (22 of 29). Episodes most frequently affected all four limbs (25 of 29) and the head and neck (21 of 29). Borborygmi were reported during episodes in 11 of 29 dogs. Episodes of vomiting and diarrhoea occurred in 14 of 29, with 50% of these being immediately before or after episodes of canine epileptoid cramping syndrome (7 of 14). Most owners (26 of 29) had changed their dog's diet, with approximately 50% (14 of 26) reporting a subsequent reduction in the frequency of episodes. CLINICAL SIGNIFICANCE This study demonstrates similarities in the phenotype of canine epileptoid cramping syndrome to paroxysmal dystonic choreoathetosis, a paroxysmal dyskinesia reported in humans. This disorder appears to be associated with gastrointestinal signs in some dogs and appears at least partially responsive to dietary adjustments.